TEOLOGI MAUT VS TEOLOGI PEMBEBASAN ASGHAR ALI ENGINEER - Putra, Rido; Amril, Amril; Rido Putra (JURNAL AL-AQIDAH, 2019)
This article describes the actions of resistance carried out by groups of adherents of "theology of death". Death theology is a theology that asks to die, but does not dare to live, outside us is wrong. Indonesia as a heterogeneous country is certainly not friendly with theology of death. If this theology develops rapidly, it will not be closed to spend Pancasila as the basis of a state that has umbrella for religion which is commonly prepared to hang from the pillars of history. Death theology received a response from contemporary Muslim theologians, one of the figures being Asghar Ali Engineer from India. Engginner's ideas are famous for "liberation theology". Engineers offer three praxis agreements in theology, namely: the concept of monotheism, the concept of faith, and the concept of jihad. These three concepts lead to the values of appreciation. This finding could be implicated in the terminology of Engginner's liberation theology as an attempt to refute the inhuman death theology with this one planet. Keywords: Death Theology, Ali Liberation Theology, Engineer Asghar, Pluralism